Electrochemical Properties and Structural Analysis of Carbon-Coated Silicon Anode for Lithium Secondary Batteries - 김형선; 정경윤; 조병원 (한국전기화학회, 2008)
The effects of carbon-coated silicon anode on the electrochemical properties and structural change wereinvestigated. The carbon-coated silicon powders have been prepared by thermal decomposition under argon/10wt%propylene mixed gas flow at 700oC. The surface and crystal structure of the synthesized materials were examinedby scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Raman spectroscopy. Lithiumcels with electrodes made from the uncoated and the carbon coated silicon anode were assembled and tested. Thecarbon-coated silicon particles merged together well after the insertion/extraction of lithium ions, and showed a rel-atively low irreversible capacity compared with the uncoated silicon particle.